Predicting intervention priorities for wildlife conflicts. Issue 1 (28th August 2019) - Baynham‐Herd, Zachary; Redpath, Steve; Bunnefeld, Nils; Keane, Aidan
Abstract: There is growing interest in developing effective interventions to manage socially and environmentally damaging conservation conflicts. There are a variety of intervention strategies that can be applied in various contexts, but the reasons one type of intervention is chosen over another remain underexplored. We surveyed conservation researchers and practitioners ( n = 427) to explore how characteristics of conflicts and characteristics of decision makers influence recommendations to alleviate conservation conflict. Using a full‐factorial design, we experimentally manipulated 3 aspects of the descriptions of 8 different wildlife‐conflict scenarios (development status of the conflict country, conflict framing, and legality of killing wild animals) and recorded which of 5 intervention types (wildlife impact reduction, awareness, enforcement, economic incentives, or stakeholder engagement) respondents prioritized. We also recorded information on respondents' demographic and disciplinary backgrounds. Stakeholder‐based interventions were recommended most often in the survey and in written feedback. However, when we fitted multinomial mixed logit models with fully completed scenario responses ( n = 411), recommendations were influenced by small changes in the details of conflict and differed according to respondent characteristics. Enforcement and awareness interventions were prioritized relatively more for conflicts in more highly developed nations and by respondents with more natural science backgrounds and relatively less experience with conflict. Contrastingly, economic interventions were prioritized more when wildlife killing was described as illegal. Age, gender, and development status of the respondent's home country also predicted some intervention decisions. Further, interrogating the influences shaping conservation decision making will further helps in the development of evidence‐informed interventions. Abstract : Article impact statement : Both the characteristics of conflicts and the characteristics of decision makers predict conflict‐intervention priorities. Abstract : Predicción de Prioridades de Intervención para Conflictos de Vida Silvestre Resumen: Existe un creciente interés en desarrollar intervenciones efectivas para gestionar conflictos de conservación social y ambientalmente dañinos. Hay una variedad de estrategias de intervención que pueden ser aplicadas en diversos contextos, pero las razones por las que se selecciona un tipo de estrategia han sido poco exploradas. Encuestamos a investigadores y a profesionales de la conservación ( n = 427) para explorar cómo influyen las características tanto de los conflictos como de los tomadores de decisiones en las recomendaciones para mitigar conflictos de conservación. Mediante un diseño factorial completo, manipulamos experimentalmente 3 aspectos de las descripciones de 8 escenarios de conflictos de vida silvestre diferentes (nivel de desarrollo del país en conflicto, encuadre del conflicto y legalidad de la matanza de animales silvestres) y registramos la priorización de 5 tipos de intervención (disminución del impacto de la vida silvestre, sensibilización, cumplimiento, incentivos económicos o participación de las partes interesadas) por los encuestados. También registramos información sobre los antecedentes demográficos y disciplinares de los encuestados. Las intervenciones basadas en las partes interesadas fueron recomendadas con mayor frecuencia en las encuestas y en la retroalimentación escrita. Sin embargo, cuando ajustamos los modelos logit mixtos multinomiales con repuestas de escenarios completos ( n = 411), las recomendaciones se vieron influenciadas por pequeños cambios en los detalles del conflicto y diferían según las características de los encuestados. Las intervenciones de cumplimiento y sensibilización fueron relativamente más priorizadas para conflictos en naciones altamente desarrolladas y por encuestados con formación en ciencias naturales y relativamente menos experiencia con conflictos. En contraste, las intervenciones económicas fueron más priorizadas cuando la matanza de vida silvestre era descrita como ilegal. La edad, el género y nivel de desarrollo del país de origen del encuestado también predijeron algunas decisiones de intervención. Una mayor profundización en las influencias que configuran la toma de decisiones en conservación promoverá el desarrollo de intervenciones basadas en evidencias. 摘要: 发展有效的干预措施来管理危害社会和环境的保护冲突已受到越来越多的关注。目前有各式各样的干预措施来应对种种情况, 但在各干预措施之间进行选择的依据仍有待探讨。为此, 我们采访了保护领域的研究者和实践者 ( n = 427), 以探究冲突的特征和决策者的特征如何影响对减轻保护冲突的实施建议。利用全因子设计, 我们设计了包含三个方面 (冲突国家的发展状况、对冲突的描述、捕杀野生动物的合法性) 的八种野生动物冲突情境的实验, 并记录了受访者在这些情境中对五种干预类型 (减缓野生动物的影响、认知、执法、经济激励, 以及利益相关者参与情况) 的选择顺序。我们还收集了受访者的人口统计学和学科专业背景的信息。结果表明, 访问调查和书面反馈中受访者首选的干预措施是利益相关者的参与。然而, 当我们用完成了所有情境应答的数据 ( n = 411) 进行多项混合逻辑回归模型拟合时, 发现受访者选择的建议会受到冲突细节的影响, 且随着受访者特征而有所不同。在更发达的国家, 或是对于有更多自然科学背景和较少冲突经验的受访者来说, 执法和认知干预更为重要。然而, 在捕杀野生动物不合法的情况下, 受访者则会优先选择经济干预。受访者的年龄、性别和所在国家的发展状况也可以预测部分干预决策。进一步探究影响保护决策的因素将有助于深入发展基于证据的干预措施。【翻译: 胡怡思审校: 聂永刚】